Spatial Variations in Vent Chemistry at the Lucky Strike Hydrothermal Field, Mid‐Atlantic Ridge (37°N): Updates for Subseafloor Flow Geometry From the Newly Discovered Capelinhos Vent. (12th November 2018) - Chavagnac, V.; Leleu, T.; Fontaine, F.; Cannat, M.; Ceuleneer, G.; Castillo, A.
Abstract: This study aims at characterizing the subseafloor architecture of the Lucky Strike hydrothermal field (LSHF) based on an extensive chemical database of the various vents. Our analysis is motivated by the discovery in 2013 of a new active high‐temperature site, named Capelinhos, approximately 1.5 km east of the LSHF. Capelinhos fluids display particular chemical features with chloride and metal (Fe and Mn) concentrations 2 times lower and 4 times higher, respectively, compared to other vent sites. Trace element partitioning over the entire chlorinity range indicates a single deep fluid source feeding all the venting sites. Applying the Si‐Cl geothermobarometer at Capelinhos, we find phase separation conditions at 435–440 °C and 370–390 bars (2, 500–2, 800 m below seafloor) consistent with former estimates for the LSHF, while temperatures of fluid‐rock last equilibrium are estimated at ~400 °C for Capelinhos and 350–375 °C for the other sites based on the Fe‐Mn geothermometer. We interpret these discrepancies in thermodynamic conditions beneath the sites in terms of crustal residence time, which are likely related to permeability variations across the hydrothermal upflow zone. We propose that conductive cooling of the upflowing fluids from the phase separation zone to the seafloor, beneath the main field vent sites, lowers the T conditions of last fluid‐rock equilibrium, enabling ~65% of Fe mobilized in the reaction zone to be stored. In comparison, Capelinhos fluids are transported more rapidly from the reaction zone to the seafloor along a high‐angle fracture system. The fluids venting at Capelinhos are more representative of the deeper part of the hydrothermal reaction zone. Key Points: Capelinhos is a new hydrothermal vent found at Lucky Strike hydrothermal vent We propose a new model of hydrothermal fluid circulation at Lucky Strike hydrothermal field Up to 65% of dissolved hydrothermal Fe is stored along the hydrothermal upflow zone